Effect of Working Capital Management on Profitability of Zenith Computers Limited: An Analysis of the Relationship between Working Capital and Profitability in Zenith Computers Limited (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Working capitalmanagement is an important aspect in firm’s financial management decision. Anoptimal working capital management is expected to contribute positively to thecreation of the firm value. To reach optimal working capital management firmmanager should control the trade off between profitability and liquidityjudiciously. Main purpose of this study is to measure the liquidity position ofthe major computers company and relationship between working capital and bankcredit to know managerial efficiency of working capital. For analyzing thedata, ratio analysis and various statistical tools and techniques were used.The data for analysis covering the period (2008-2012) is collected from thefinancial statements published in the annual reports. It was found that theposition of working capital management of the company is very sound. It is alsofound that there is insignificant positive relationship between working capitaland bank credit.